The effect of road-based mortality on a local population of newts along a narrow two-lane road in California - Wilkinson, Jeffery A.; Romansic, John M. (Frontiers in Ecology and Evolution, 2022)
Numerous studies have documented high numbers of amphibians killed by vehicular strikes on roads. This direct mortality can cause population declines and extirpations, but in some cases the declines might be masked, initially, by large population sizes. Population viability analysis can help discern population trajectories and identify incipient declines. We applied this tool to a situation in Santa Clara County, California where a dead-on-the-road carcass survey in 2017 demonstrated that a large number of newts in the genus Taricha were being killed by vehicles using a small two-lane road (Alma Bridge Road) most likely during annual breeding migrations to a local reservoir (Lexington Reservoir). To help determine the effect of this road-based mortality on the California newt (T. torosa) population, we conducted a drift fence/pitfall trap array study on the road during the 2020-2021 breeding season. Drift fence/pitfall trap arrays were installed at six locations along a 6.6-km stretch of the road and daily surveys were conducted at these arrays over a 148-day period from mid-November to end of March. Daily traffic and precipitation data were also recorded to help inform timing of proposed mitigation efforts. Concurrently, a group of community scientists conducted a dead-on-the-road carcass survey over the entire 6.6-km study area. We calculated the number of adult newts attempting to cross Alma Bridge Road at the arrays and the associated road-based mortality rates. Then, we combined our array results with road mortality data provided by the community scientists to estimate the number of adult California newts attempting to cross the road and their mortality rates over the entire study area during the survey period. We then incorporated this data into a population viability model to determine whether this road-based mortality rate might, if left unabated, lead to a reduction in, and possibly the eventual extirpation of, the local population of T. torosa breeding in Lexington Reservoir. The model indicated that this population would be extirpated in approximately 92 years. Because the road has been in use for approximately 67 years, we discussed possible reasons why this population is currently extant and experiencing this high level of road-based mortality.